HIV and syphilis knowledge, perceptions, and practices among Myanmar migrant workers in Samut Sakhon Province, Thailand - Alfrison Paloga; Dumrongkiet Arthan; Pannamas Maneekan; Patreeya Kitcharoen; Apichai Wattanapisit; Chirawat Paratthakonkun; Suparat Phuanukoonnon; Shoon Lei Nyan Wai Tun; Ngamphol Soonthornworasiri (BMC, 2022)
Abstract Background Thailand has been one of the largest migration hubs in Southeast Asia for the past four decades and keeps attracting migrants from neighboring countries. Due to difficulties associated with their status, migration can place individuals at a heightened risk for sexually transmitted diseases. This study aimed to examine factors influencing HIV and syphilis preventive behaviors among Myanmar migrants in Samut Sakhon, Thailand. Methods A cross-sectional mixed-method study was conducted among Myanmar migrants aged 18 years and above in Samut Sakhon Province, Thailand. To fulfill this study's aims, four hundred seventy-three respondents completed a survey to provide quantitative data, and eight participants completed in-depth qualitative interviews. The factors associated with protective sexual behaviors were identified with multiple logistic regression analysis of the quantitative study data and thematic analysis of the qualitative data. Results The respondents showed good knowledge of HIV and syphilis (50.1%), but over half (55.6%) exhibited the negative perception of sexually transmitted disease prevention; about 81.4% of male respondents never used a condom when they had sexual intercourse in the past year. Based on multivariate analysis, income expenses-balance (adjusted odds ratio (AOR) = 2.379, 95% confidence interval (CI): 1.002-5.731, p = 0.049), number of sex partners (AOR = 3.044, 95% CI: 1.339-6.924, p = 0.008), and having sex with a prostitute (AOR = 6.085, 95% CI: 1.28-28.918, p = 0.023) were all statistically associated with unprotected sex. In the qualitative analysis, knowledge, understanding, beliefs; the influence of culture, community, and environment; and condom perceptions were also important factors. Conclusion Low use of condoms in sexual practice was identified, and the appropriate intervention or approach to improve the utilization of condoms in the community was provided.